Infiltrative ophthalmopathy and primary hypothyroidism: a rare clinical manifestation of a common disease. Issue 999 (24th February 2009) - Rajput, R; Dhingra, A; Kumar, K; Sen, J
Abstract : The association of infiltrative ophthalmopathy with primary hypothyroidism is uncommon. We describe two such cases manifesting at different times during the course of primary hypothyroidism. The successful outcome of the present cases suggests that the timely addition of levothyroxine treatment alone or in combination with steroids is useful and effective in the management of hypothyroid Graves' ophthalmopathy.